KEUNTUNGAN RELATIF, KESIAPAN ORGANISASIONAL, PENGADOPSIAN SISTEM E-COMMERCE DAN KINERJA PERUSAHAAN - Ikhsan, Adhisyahfitri Evalina; Razki, Cut Danisha (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2016)
This study aimed to examine the effect of Relative Advantages and Organizational Readiness to Adoption of E-commerce system on SMEs in Banda Aceh and its implications for company performance. The population in this study are travel agencies who are registered as members of ASITA in Banda Aceh. Respondents in this study include leadership of the company or the companys operations manager of the travel agency. The data used in this research is primary data and data collection was done by direct circulate a questionnaire containing statements related to the studied variables to the respondent. Data were analyzed using linear regression. The results showed Relative Advantage has a negative influence on the adoption of e-commerce system. Organizational Readiness positive effect on the adoption of the system E-commerce and E-commerce System Adoption positive effect on company performance.